Pelatihan Komputer Bagi Guru SMP Taman Rama Jimbaran - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung; Eka Ayu Purmana Lestari (Warmadewa Press, 2021)
This social engagement is done in order to improve understanding and performance of the teachers of Taman Rama Jimbaran Junior High School (TRJ-JHS) where there is no teachers that have the background study in Informatics and Technology. There are only 5 classes n TRJ-JHS. This small numbers of classes has caused less number of teaching periods. The solution to solve this problem is by assigning the teachers to teach other subjects that were not their background of study before. Based on the regulation of Educational Ministry Number 15 Year 2018, verse 4 poin 3 stated that “The implementation of learning process is 24 period per week as the minimum total and 40 periods per week as the maximum total. This lack of knowledge has made teachers found difficulties especially regarding the topics about Algorithm and programs. Purposes of study are to improve the level of knowledge and performances also it will enable the teachers to teach the students appropriately based on the competency gained. Method used was online conference through Ms Team. Main findings of this social engagement are: the eagerness of the Principal and teachers of TRJ-JHS to improve level of knowledge and performances by giving feedback through practices. There were 2 times evaluations after 3rd and 4th meetings by reconsidering difficulties on the process. The teachers are able to understand the topics especially on Algorithm and the skills in making and editing the learning videos. The results of pre-test and post-test has shown the improvement where at the pre-test out of 20 participants, 16 failed while 4 passed the passing score 76 and the results of post-test was all participants can get the scored 76 and above. Finally, this improvement is expected to be applied properly and appropriately for students especially for the subject Informatics and technology.